Ta có : \(B=\frac{\sqrt{x}-2+5}{\sqrt{x}-2}=1+\frac{5}{\sqrt{x}-2}\)
Mà B nguyên nên \(\frac{5}{\sqrt{x}-2}\in Z\)hay \(\left(\sqrt{x}-2\right)\inƯ\left(5\right)\)
\(\sqrt{x}-2\) | 1 | -1 | 5 | -5 |
\(\sqrt{x}\) | 3 | 1 | 7 | -3 |
\(x\) | 9 | 1 | 49 | \(\varnothing\) |
Vậy \(x\in\left(1;9;49\right)\)
\(B=\frac{\sqrt{x}+3}{\sqrt{x}-2}\) \(ĐKXĐ:x\ne4;x\ge0\)
\(B=\frac{\sqrt{x}-2+5}{\sqrt{x}-2}\)
\(B=1+\frac{5}{\sqrt{x}-2}\)
để \(B\in Z\)thì \(x\in Z\)
mà \(1\in Z\forall R\) nên \(\frac{5}{\sqrt{x}-2}\in Z\)
\(\Leftrightarrow\sqrt{x}-2\inƯ\left(5\right)\)
\(\Leftrightarrow\sqrt{x}-2\in\left\{\pm1;\pm5\right\}\)
mà \(x\ge0\) nên \(\sqrt{x}-2\in\left\{1;5\right\}\)
+ \(\sqrt{x}-2=1\) \(\Leftrightarrow\sqrt{x}=3\Leftrightarrow x=9\) (thỏa mãn )
+ \(\sqrt{x}-2=5\Leftrightarrow\sqrt{x}=7\Leftrightarrow x=49\) ( thỏa mãn)
vậy \(x\in\left\{9;49\right\}\) thì \(B\in Z\)